Strategies for Reducing Employee Turnover in Small- and Medium-Sized Enterprises - Kate S Andrews; Tijani Mohammed (Westcliff University, 2020)
Employee turnover leads to increased operational costs and workloads and affects sales performance. Reducing employee turnover is essential for managers of small and medium sized enterprises to minimize costs and increase sales performance. Grounded in the job embeddedness theory, the purpose of this qualitative multiple case study was to explore strategies the managers of small and medium sized enterprises use to reduce employee turnover that negatively affects sales performance. Data were collected using semistructured, face-to-face interviews, and a review of organizational documents. The participants consisted of three managers of small and medium sized enterprises in the Bronx, New York. After conducting the interviews, the interviews were transcribed. The transcripts and organizational documents were then uploaded into NVivo v12 software to analyze the data (i.e., organize data, create codes, and identify themes). The analysis revealed that recognition and rewards, training and career advancement opportunities, effective communication, and pay, compensation, and benefits are effective in helping to reduce employee turnover. Managers of small and medium sized enterprises may use the findings to devise recognition and reward strategies to decrease employee turnover. The findings and recommendations from this inquiry may help managers of small and medium sized enterprises, business leaders or owners, and human resource personnel to reduce employee turnover and improve sales performance, profitability, and competitiveness.